Comparing Methods for Microplastic Quantification Using the Danube as a Model - Kiefer, Tim; Knoll, Martin; Fath, Andreas (Microplastics, 2023)
This study investigates the impact different mesh-sized filtration methods have on the amount of detected microplastics in the surface water of the Danube River delta. Further, the distribution of microplastics in different size categories (20 µm, 65 µm, 105 µm) and in the water column (0 m, 3 m, 6 m) was analyzed. Our findings show that the Danube River carries 46 p∙L−1 (microplastic particles per liter) with a size larger than 105 µm, 95 p∙L−1 larger than 65 µm and 2677 p∙L−1 that are larger than 20 µm. This suggests a negative logarithmic correlation between mesh size and particle amount. The most abundant polymer throughout all samples was polyethylene terephthalate, followed by polytetrafluorethylene. Overall, the data shows that different sampling methods cannot be compared directly. Further research is needed to find correlations in particle sizes for better comparison between different sampling methods.